A system-level multi-field coupling algorithm for regenerative cooling thrust chamber of a LOX/methane rocket engine - Yan, Zelong; Chen, Yang; Wu, Youliang; Liu, Ziyan; Gao, Yushan; Wang, Weizong (Acta astronautica, 2023)
A systematic and hierarchical multi-physics coupling simulation method is proposed to model the combustion, combustion-gas transonic flow, coolant transcritical flow, and transient heat transfer phenomena inside the regenerative cooling thrust chamber subsystem of a LOX/methane rocket engine. By combining this algorithm with a self-developed platform, two distributed parameter modules are developed. Based on the ground test conditions of a LOX/methane engine, a verification case is established, and transient simulation studies are conducted. Comparisons with steady-state test data show that the calculated errors for coolant temperature rise and pressure drop are not higher than 4%. The simulation results reveal the locations where the transition from liquid to supercritical state occurs within the cooling jacket and provide three peril points of wall temperature on the thrust chamber. This study comprehensively reveals the occurrence of transcritical transient processes inside the cooling channels during the regenerative cooling process, laying the foundation for future entire system simulation. •A finite volume model system for system-level transient transcritical fluid flow.•Fundamental equation of state.•Transonic flow, transcritical flow, heat transfer, and combustion multi-physics coupled.•Modeling regenerative cooling thrust chamber of a LOX/methane rocket engine.